A case involving the spontaneous reduction of an ameloblastic fibroma - Yasuaki Mekaru; Ueda Gousei; Higa Tsutomu; Kouchi Masato; Tatetsu Masaharu; Irei Mitsutaka (Journal of Dentomaxillofacial Science, 2017)
Objective: Ameloblastic fibroma is an uncommon type of mixed odontogenic tumor. It is caused by the growth of the odontogenic epithelium and mesenchymal tissue and can have adverse effects on the formation of dental structures. It usually arises in the mandible, but cases involving the mandibular ramus are rare.Methods: Here, we report a case of ameloblastic fibroma in the right mandibular ramus involving a 15-year-old male patient. According to panoramic X-ray examinations, the tumor shrank spontaneously in the 3 years before surgery (from approximately 80mm×55mmto 50mm×25mm).Results: A histological evaluation revealed the proliferation of odontogenic epithelial tissue and mesenchymal elements. The Ki-67 index of the lesion was 0%.Conclusion: Cases of ameloblastic fibroma involving patients aged ≥ 22 years old are very likely to recur and undergo malignant changes.